Implementasi Terapi Menggenggam Bola Karet Bergerigi Dalam Asuhan Keperawatan Pada Ny. Z Dengan Stroke Non Hemoragik Di Rumah Sakit Islam Malahayati Medan - Riska Amelia; Rafika Nur Siregar (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2025)
Stroke is a term used to describe neurological changes caused by a disruption in the blood supply to part of the brain. Stroke can cause a decrease or even loss of function controlled by these tissues, one of the symptoms that arises is muscle weakness in the affected body parts such as the fingers. Stroke is a clinical sign that develops rapidly due to focal or global brain function disorders, it can cause death for no other cause than vascular. One way to increase muscle strength and help recovery of extremities is by holding a serrated rubber ball therapy. This article uses a case study design and the subjects used in this case are patients with non-hemorrhagic stroke disorders who are treated at RSI Malahayati Medan with nursing problems of impaired physical mobility due to muscle weakness in the extremities. The results of implementing the intervention showed that after the serrated rubber ball grasping therapy was carried out for 4 days, it was carried out 2 times in 1 day with a duration of 7-10 minutes. After 4 days of intervention, muscle strength of 5-4 was obtained. Conclusion: The application of the serrated rubber ball grasping therapy technique in non-hemorrhagic stroke patients can be used to help increase muscle strength. Suggestion: It is hoped that patients can carry out independent therapeutic actions by holding a serrated rubber ball when they experience weakness in the muscles of the extremities.